We are better together - McKibben, Bill; Lewis, Stevie (New York : Godwin Books, Henry Holt and Company, 2022)
From environmentalist and bestselling author Bill McKibben comes a hopeful, inspiring picture book celebrating the power of human cooperation and the beauty of life on Earth.
School Library Journal starred, January 2022
3.6
K-3
AD650L
Keywords: Environmental protection -- Citizen participation -- Juvenile literature; Climate change mitigation -- Juvenile literature; Climatic changes -- Juvenile literature; Cooperation -- Juvenile literature; Environmental protection -- Citizen participation; Climate change mitigation; Climatic changes; Cooperation